2002
DOI: 10.1046/j.0300-0664.2001.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin B in boys from birth to adulthood: relationship with age, pubertal stage, FSH and testosterone

Abstract: The two peaks of inhibin B during infancy and early puberty appear to reflect the two periods of Sertoli cell proliferation in normal human males. During mid-childhood, a relatively constant amount of inhibin B is secreted constitutively. The early FSH-independent increase in inhibin B that precedes clinical puberty and continues to stage G2 may be stimulated by testosterone or other factors from Leydig cells. The inverse relationship between inhibin B and FSH that subsequently develops from mid-puberty onward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
5
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 23 publications
10
74
5
9
Order By: Relevance
“…Mean concentrations increase slightly between pre-puberty and the early stage of puberty, but then increase markedly into mid-puberty. Similar patterns during puberty have been reported by others (2,4,5). The most marked diurnal rhythm was observed during early and in mid pubertal development.…”
Section: Discussionsupporting
confidence: 71%
“…Mean concentrations increase slightly between pre-puberty and the early stage of puberty, but then increase markedly into mid-puberty. Similar patterns during puberty have been reported by others (2,4,5). The most marked diurnal rhythm was observed during early and in mid pubertal development.…”
Section: Discussionsupporting
confidence: 71%
“…In both sexes, FSH secretion is stimulated by GnRH and inhibited by inhibin and, in women, also by estrogens. The normal range of inhibin B levels is much higher in males than females at all ages (20,(29)(30)(31); E 2 levels in women with normal ovarian function are much higher than in men, while FSH levels are similar in both sexes. We suggest that the common cause of hypogonadism in most PWS patients, both males and females, is related to a unique defect in inhibin B secretion.…”
Section: Discussionmentioning
confidence: 92%
“…This has been determined through characterization of their normal expression levels. Inhibin B expression, for example, is high in infant boys but declines in concert with the increase in gonadotrophins, reaching a nadir at 6-10 years of age (Crofton et al 2002). Byrd et al (1998) consequently suggested that inhibin B could potentially be used as a biomarker in the diagnosis of cryptorchidism and precocious puberty.…”
Section: Molecular and Cellular Biomarkers Of Pubertymentioning
confidence: 99%